Yearbook of the European Convention on Human Rights / Annuaire de la convention européenne des droits de l'homme, Volume 62 (2019) (Yearbook of the European Convention on Human Rights / Annuaire de la convention européenne des droits de l'homme ;, 2020)
The Yearbook of the European Convention on Human Rights, edited by the Directorate General of Human Rights and Legal Affairs, is an indispensable record of the development and impact of the world's oldest binding international human rights treaty. It reviews the implementation of the Convention both by the European Court of Human Rights and by the Council of Europe's Committee of Ministers, responsible for supervising the application of the Court's judgments in the member states. The Yearbook includes: Full text of any new protocols to the Convention as they are opened for signature, together with the state of signatures and ratifications. Full listing of Court judgments; judgments broken down by subject-matter; and extensive summaries of key judgments handed down by the Court during the year. Selected human rights (DH) resolutions adopted as part of the Committee of Ministers' work supervising the execution of the Court's judgments. Enquiries by the Secretary General carried out under Article 52 of the Convention. Other work of the Council of Europe connected with the European Convention on Human Rights, carried out by the Committee of Ministers, the Parliamentary Assembly, and the Directorate General of Human Rights and Legal Affairs. Bibliographic information from the library of the European Court of Human Rights. The Yearbook is published in an English-French bilingual edition.